Rethinking Marx rethinking the public - Higgins, John (University of the Free State, 2014)
This essay argues that the young Marx’s defence of press freedom in the repressive Germany of his day is more important than the tradition of Orthodox Marxism has generally allowed, and is best considered as a crucial constitutive feature of the massively influential career as critical thinker and political activist to come. Furthermore, it is in and through Marx’s reconfiguring of the idea of the public in these early writings that his work may make a significant contribution to today’s most pressing debates around the practice and elusive ideal of democracy, and notably those in South Africa involving the so called Freedom of Information bill.
Keywords: Marx, Karl; Press freedom; Democracy